Post resuscitation care – some words of caution and a call for action - Søreide, Eldar; Larsen, Alf Inge (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2015)
This fall the European Resuscitation Council (ERC) and the European Cardiology Society (ESC) publish updated post resuscitation care guidelines. For these guidelines to have an impact they must be implemented into daily clinical practice. Newer studies imply that differences in hospital care explain much of the observed differences in survival after out-of-hospital cardiac arrest. A recent Nordic (Denmark, Finland, Iceland, Norway, Sweden) survey suggests worrisome variations in post resuscitation care provided and should urge us all to act in the coming years. One important step will be to build up resuscitation systems with integrated cardiac arrest centres in all the 5 Nordic countries and benchmark process of care, financial implications and survival. publishedVersion